(untitled) (International journal of artificial intelligence, 2026)
This article provides a comprehensive analysis of the impact of the tax burden on economic development, using the example of Uzbekistan’s tax system as of 2026. The study examines the legal, economic, and institutional dimensions of taxation, focusing on how the level and structure of the tax burden influence investment activity, business performance, fiscal sustainability, and income distribution. The research is based on the provisions of the current Tax Code of the Republic of Uzbekistan, official statistical data, and modern theoretical approaches in public finance.